Use of the MA-XRF Technique in the Authentication of Guignard’s Artwork Recovered by the RJ Civil Police - Nilton Thaumaturgo Rocha Junior; Claudia Regina Ferreira de Souza; André Rocha Pimenta; Valter de Souza Félix; Renato Pereira de Freitas (Semina: Ciências Exatas e Tecnológicas, 2025)
Artworks are frequently implicated in the commission of crimes of money laundering, fraud, corruption and robbery/theft. On August 10, 2022, Operação Sol Poente (Operation Setting Sun), launched by the Civil Police of Rio de Janeiro, recovered seventeen artworks stolen from the Boghici Collection. Among them was the Menino [Boy] (1935), by Guignard. For this reason, forensic examinations were conducted to verify the authenticity of the recovered artworks. Therefore, macro X-ray fluorescence scanning (MA-XRF) was employed as a portable and non-invasive technique to obtain elemental maps of the chemical composition present in the paint layers. The objective of this study was to demonstrate the potential of the MA-XRF technique in the context of a high-profile criminal investigation. Elemental mapping was conducted using the portable MA-XRF system, model CRONO (Bruker), on both the authenticated and unauthenticated artworks. The resulting elemental distributions exhibited significant similarities, indicating consistency in the materials and techniques used in their production. These results indicate similarities in the creation process and materials of the paintings. Although the authentication of artworks remains a complex and multidisciplinary process, the results of this study underscore the value of MA-XRF as a forensic tool capable of providing valuable insights in the resolution of forensic cases.